New Azo-Thiadiazole Ligands (Preparation, Spectral, Thermal, Biochemical, Physical properties) - Studying - Nagham Mahmood Aljamali (Journal of Global Pharma Technology, 2018)
Azo-Thiadiazole dyes were prepared as a new ligands from aminothiazole compound. The reaction started with coupling step of hydroxyl benzoic acid , then cyclization step of thiosemicabazide to produce thiadiazole derivative , flowed by reaction with dicarbonyl compounds to yield azo- thiadiazol ligands. Our new azo ligands investigation by many chemical techniques represented by ( I.R, H.NMR, Mass )- spectra and studied their behavior (Thermal , Biochemical ) with Physical properties . Keywords: Thiazole, Thiadiazol , Cyclization , Esterification , Azo , Sulphobenzoic acid.